Unencumbered by style: Why do funds change factor loadings, and does it help? - Bai, Ting; Hilscher, Jens; Scherbina, Anna (Journal of Banking & Finance, 2025)
We show that, rather than maintaining a constant style, active equity funds alter their factor loadings over time. Style changes are larger following quarters in which funds either substantially under- or out-perform other funds based on returns or fund flows, which is explained by managers both not correcting the resulting passive style drift and deliberately reallocating a portion of the portfolio. Motivated by this observation, we identify a new measure of manager skill, which we call “tactical investment skill.” It captures a manager’s ex-ante observable ability to increase future returns through loadings changes. We show that high-skill managers outperform their low-skill peers in the following month in terms of raw returns and alphas. This outperformance is more pronounced following quarters with large loadings changes.